Quantitative Analysis of Dual-Purpose, Patient-Specific Craniofacial Implants for Correction of Temporal Deformity. Issue 2 (14th February 2015) - Zhong, Shuting; Huang, Gary J; Susarla, Srinivas M; Swanson, Edward W; Huang, Judy; Gordon, Chad R
Abstract: BACKGROUND: The development of computer-assisted design, virtual modeling, and computed tomography has allowed precise customization of implants for patients who undergo neurosurgical or craniofacial surgery procedures. However, such techniques and implant designs have not adequately addressed temporal asymmetry due to postoperative bone resorption, temporalis muscle malposition/foreshortening, and/or temporal fat pad atrophy. OBJECTIVE: We hypothesized that an alteration in customized craniofacial implant (CCI) design with a strategic extension inferolaterally and excessive material bulking would provide simultaneous reconstruction of coexisting temporal skull defects and therefore reduce the effect of soft tissue deformities. METHODS: A single-surgeon, single-institution retrospective cohort study was performed to include 10 consecutive subjects who underwent cranioplasty reconstruction with modified implants during a 3-year period. Implants were placed with the use of our previously described pericranial-onlay technique. With the use of a computed tomography-based, computer-assisted design/manufacturing methodology, novel dual-purpose implants were designed to prevent and/or correct persistent temporal hollowing. The efficacy of the new CCI shape and design for cranial restoration of temporal symmetry was analyzed in both 2 and 3 dimensions. RESULTS: In 2-dimensional analyses, the modified implant provided enhanced lateral projection (21%; 1.06 cm) in areas closest to the temporal arch. Three-dimensional volumetric analyses demonstrated that additional bulking totaled 24 ± 11 cm 3 (range, 9-43 cm 3 ), which essentially replaced 40 ± 13.7% (range, 26%-60%) of the absent temporal volume contributing to persistent temporal hollowing. CONCLUSION: Computer-designed, dual-purpose CCIs can be safely created with unprecedented shape to prevent and/or eradicate postoperative temporal deformity.